Hybrid mass spectrometry approaches in glycoprotein analysis and their usage in scoring biosimilarity - Yang Yang (Nature Portfolio, 2016)
Many biopharmaceuticals exhibit mixed heterogeneity in their post-translational modifications (PTMs) that are essential for their function. Here the authors use a combination of mass spectrometry techniques to analyse human erythropoietin (EPO) and properdin to discover new PTMs on properdin and derive a biosimilarity score for various sources of EPO.